A study for the longitudinal permeability of fibrous porous media with consideration of electroviscous effects. (June 2022) - Liang, Mingchao; Yang, Shanshan; Pang, Minghua; Wang, Zhankui; Xiao, Boqi
Abstract: We investigate theoretically the longitudinal permeability for the electroviscous flow through one-dimensional (1D) fibrous porous media with orderly and disorderly fiber arrays. The structures of fibrous porous media are idealized as circular unit cells. In the cell, the dimensionless net charge density is given by solving the linearized Poisson-Boltzmann equation, and is approximated as 1 by detailed discussions. Based on the approximate value of the net charge density, circular unit cell and Voronoi Tessellation method, we propose mathematical models for the longitudinal permeability with considering electroviscous effects. The effects of the fiber volume fraction, fiber radius and electroviscous resistance number on the longitudinal permeability are analyzed in detail. Moreover, there are good agreements between the present predictions and these results from the literatures. Graphical Abstract: ga1